Use of sneaker rush and symptoms occurrence of skeletal muscle (SME) in Ballerina - Araújo, Lia Grego Muniz de [UNESP]; Fernandes, Rômulo de Araújo [UNESP]; Pastre, Carlos Marcelo [UNESP]; Monteiro, Henrique Luiz [UNESP] (FapUNIFESP (SciELO), 2013)
Introduction: Technical literature shows high frequencies of injuries occurring in classical ballet dancers; however, only limited information about the permanent effects of chronic diseases are mentioned. Objective: To compare the presence of MSD among dancers who wear pointe shoes and those who do not. Methods: The research was conducted at the 27th Festival of Joinville in Santa Catarina. The study had the participation of 111 dancers, 88 of whom wore pointe shoes while 23 did not. Specific procedures were used to obtain information related to MSD and foot injuries caused by dancing. Results: The most affected parts were the knees (29.7% with pointe shoes versus 39% without), spine (26.4% with pointe shoes versus 22% without), and ankle/foot (20% with pointe shoes versus 12.2% without). Through odds ratio and respective confidence intervals (IC95%), the study identified protection factor in the knees (0.24; CI95% - 0.09-0.64) and legs (0.11; CI95% - 0.02-0.65) for dancers who wear pointe shoes. It was found that the risk of injuries in specific structures of the foot is significantly higher among those dancers. In this case, the appearance of bunions (9.74; CI95% - 1.25-75,99), calluses on the toes (3.46; CI95% - 1.29-9.27) and the association of the three (4.47; CI95% - 1.69-11.83) were those that showed an increased risk factor compared to dancers who do not stand en pointe. Conclusion: The use of pointe shoes in elite Brazilian dancers was associated to lower occurrence of MSD in the knee and leg, however it was strongly associated to foot injuries.
Keywords: Injuries; Musculoskeletal system; Pain